A facile spray drying route for mesoporous Li3VO4/C hollow spheres as an anode for long life lithium ion batteries. Issue 19 (22nd April 2016) - Yang, Yang; Li, Jiaqi; He, Xinyi; Wang, Jing; Sun, Dong; Zhao, Jinbao
Abstract : A facile route, involving a spray drying method and subsequent heat treatment process, for preparing mesoporous Li3 VO4 /C hollow spheres has been developed. The unique structure of the LVO/C offers a synergistic effect to reduce Li + ion diffusion paths and facilitate the transfer of electrons and electrolytes during prolonged cycling. Abstract : Mesoporous Li3 VO4 /C hollow spheres have been prepared by a facile drying method and subsequent heat treatment process. The unique structure of the composite offers a synergistic effect to facilitate the transport of Li + ions and electrons and afford an anode with superior rate capability and cyclic stability.